Questioning the Stakeholders' Perceptions To The Availability of Facilities for Disability Tourism: A Case Study in Bunaken Island - Towoliu, Benny Irwan; Bernadain Dainty Polii; Dianne O. Rondonuwu; Maryke Alelo; Diane Tangian (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
Inclusive tourism remains a challenge in Indonesia, particularly in marine destinations such as Bunaken Island, where accessibility and facilities for people with disabilities are lacking. This study aims to explore stakeholder perceptions, including government officials, tourism businesses, and local communities, regarding the availability and need for disability-friendly tourism infrastructure in Bunaken. A mixed-method approach was applied, combining quantitative surveys of 321 respondents with qualitative interviews and field observations. The findings reveal that stakeholders strongly agree (>4.1) on the urgency of providing access for disabled tourists and moderately agree (>3.7) on the importance of supporting facilities, including accessible toilets, communication aids, and modified transport. However, some respondents raised concerns related to renovation costs and implementation feasibility. The study concludes that inclusive tourism in Bunaken is both necessary and economically promising. Specific recommendations include prioritizing basic accessible infrastructure, engaging disabled persons organizations (DPOs) in planning, and leveraging public-private partnerships to fund improvements. This research contributes to the discourse on sustainable and inclusive tourism by offering empirical insights and practical strategies to make Bunaken Island a more accessible and welcoming destination for all.